Business Duration Strengthens Capital and Cost Management for MSME Profitability - M. Syamsudin Al Hanafi; Heri Widodo (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Micro, Small, and Medium Enterprises (MSMEs) play a vital role in sustaining village economies and community livelihoods in Indonesia. Specific Background: Sayangan MSMEs in Kebakalan and Kesambi Villages represent hereditary manufacturing businesses facing challenges in managing capital, production costs, and sales turnover to achieve stable profitability. Knowledge Gap: Prior studies show inconsistent findings regarding how these factors relate to profitability, particularly regarding the role of business duration as a moderating variable in village-based MSMEs. Aim: This study examines the relationships between business capital, production costs, and sales turnover with profitability, while positioning business duration as a moderating factor. Results: Findings reveal that capital and sales turnover are positively associated with profitability, production costs are significant, and business duration strengthens the relationships between capital and costs with profitability but not between sales turnover and profitability. Novelty: The study integrates business duration as a moderating variable within a localized village MSME context, providing a community-based managerial perspective. Implications: Results offer practical guidance for MSME actors to prioritize efficient cost control, optimal capital use, and experiential learning to maintain sustainable profitability in rural enterprises.